Cognitive Assessment in Coached Learning Environments - Frederiksen, Carl; Donin, Janet (Alberta Journal of Educational Research, 1999)
An approach to cognitive assessment of problem-solving in complex computer-based tutorial environments is described. The approach is based on studies of expert tutoring and students' performance in natural tutoring situations in specific domains such as engineering and statistics. A model of expert tutors' knowledge in a domain of applied statistics was developed and used as a basis for a web-based computer coach that emulates human tutoring. Cognitive assessments are obtained from records of students' actions as they learn to apply particular components of the procedural knozvledge required to solve problems in the domain with the help of the computer tutor. Learning is evaluated by studying changes in these records of performance as students practice successive problem exercises. These assessments can then be used subsequently to predict students' unassisted performance in solving post-instruction transfer problems.